Partial pressure (or fugacity) of carbon dioxide, salinity and other variables collected from Surface underway observations using Carbon dioxide (CO2) gas analyzer, Shower head chamber equilibrator for autonomous carbon dioxide (CO2) measurement and other instruments from LAURENCE M. GOULD in the North Pacific Ocean, South Atlantic Ocean and others from 2004-12-31 to 2005-12-26 (NCEI Accession 0144531) - Takahashi, T., C. Sweeney and S. C. Sutherland (NOAA NCEI Environmental Data Archive, 2016)
NCEI Accession 0144531 includes Surface underway data collected from LAURENCE M. GOULD in the North Pacific Ocean, South Atlantic Ocean, South Pacific Ocean and Southern Oceans (> 60 degrees South) from 2004-12-31 to 2005-12-26. These data include BAROMETRIC PRESSURE, Partial pressure (or fugacity) of carbon dioxide - water, SALINITY and SEA SURFACE TEMPERATURE. The instruments used to collect these data include Carbon dioxide (CO2) gas analyzer and Shower head chamber equilibrator for autonomous carbon dioxide (CO2) measurement. These data were collected by Taro Takahashi and Stewart Sutherland of Columbia University; Lamont-Doherty Earth Observatory and Colm Sweeney of University of Colorado at Boulder; Cooperative Institute for Research In Environmental Sciences as part of the VOS_LMG_Lines_2005 data set. CDIAC associated the following cruise ID(s) with this data set: 33LG20041231 The Global Volunteer Observing Ship (VOS) Program is coordinated by the UNESCO International Ocean Carbon Coordination Project (IOCCP). International groups from 14 countries have been outfitting research ships and commercial vessels with automated CO2 sampling equipment to analyze the carbon exchange between the ocean and atmosphere.